Antifouling membrane integrated renewable gold microelectrode for in situ detection of As(iii)1. Issue 18 (21st September 2015) - Touilloux, Romain; Tercier-Waeber, Mary-Lou; Bakker, Eric
<x xml:space="preserve">Abstract</x> Arsenic is of a global concern because of the widespread, chronic poisoning found in a number of countries and affecting large populations. A gel integrated microelectrode sensing approach for arsenic(iii) is shown here to fulfill the requirements for direct measurements of (oxy)anions in freshwaters.